Train Obstacle Detection System Using Avr Microcontroller and SR04 Ultrasonic Sensor - A.A. Aziz; W.R.W. Ahmad (Institute of Advanced Engineering and Science, 2018)
In Malaysia, railway is considered as the backbone of transport, connecting people from all across the country. With the current state of economy, more people prefer to choose train as main transportation especially in big city area such as Kuala Lumpur. With lower cost and relatively the safest form of transports compared to the other transports, like cars, motorcycles or busses, it is a wise choice to use train as daily commute transport. Nowadays, the rail traffic network in Malaysia are getting busier with trains traveling at higher speeds and carrying more passengers with heavier axle loads than before. With the increase of passenger, the risk involved in daily train operation will significantly increase. An improved safety system is required to keep up with the ever growing train loads. The proposed safety system is applied to alert the train operators. The whole system is comprised of an ultrasonic sensor connected to a database and an Atmega328P microcontroller mounted on a custom PCB board. It is found that the train in this country requires a distance of 77 meter in order to completely stop the train with regards to a few assumptions on the average mass and the speed of the train.